HUBUNGAN SERUM TRANSAMINASE DENGAN SINDROM SYOK DENGUE - , MD. Yoga Putra Susana, dr. Bagus Ngurah Putu Arhana, Sp.A(K). ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Dengue is a viral disease that borned by mosquito vector which has rapid spread around the world. The incidence has increased more than 30 fold in the last 50 years. Clinical manifestation of dengue is vary from subclinical stage to dengue shock syndrome. Dengue viral infection leads to inflammation process indeed cause liver injury. Study between transaminase serum and severity of dengue infection has been widely reported, but its association is remain controversial. The aim of this study is to evaluate association between transaminase serum and dengue shock syndrome. A nested case control study, conducted by collecting data from patient diagnosed with suspect dengue infection and hospitalized in Sanglah Hospital. Patient were observed during the treatment according to standard medical care for dengue infection. Case group was patient diagnosed with DSS, and control group was patient disagnosed else than DSS (DF, DHF I and DHF II). Serum was taken for AST and ALT examination during the first day of treatment. Hematocrit, leucocyte count, hemoglobin, and platelete data were collected on the first day of treatment based on the highest hematocrite value. Data were analized by using biavariate and multivariate method with level of confidence Î± = 0.05.